In situ NMR reveals a pH sensor motif in an outer membrane protein that drives bacterial vesicle production - Nicholas A. Wood; Alyssa Kraft; Kyungsoo Shin; Tata Gopinath; Francesca M. Marassi (Proceedings of the National Academy of Sciences, 2025)
The outer membrane vesicles (OMVs) produced by diderm bacteria have important roles in cell envelope homeostasis, secretion, interbacterial communication, and pathogenesis. The facultative intracellular pathogen Salmonella enterica Typhimurium (STm) activates OMV biogenesis inside the acidic vacuoles of host cells by upregulating the expression of the OM protein PagC, one of the most robustly activated genes in a host environment. Here, we used solid-state nuclear magnetic resonance (NMR) and electron microscopy (EM), with native bacterial OMVs, to demonstrate that three histidines, essential for the OMV biogenic function of PagC, constitute a key pH-sensing motif. The NMR spectra of PagC in OMVs show that they become protonated around pH 6, and His protonation is associated with specific perturbations of select regions of PagC. The use of bacterial OMVs is a key aspect of this work enabling NMR structural studies in the context of the physiological environment. PagC expression upregulates OMV production in Escherichia coli , replicating its function in STm. Moreover, the presence of PagC drives a striking aggregation of OMVs and increases bacterial cell pellicle formation at acidic pH, pointing to a potential role as an adhesin active in biofilm formation. The data provide experimental evidence for a pH-dependent mechanism of OMV biogenesis and aggregation driven by an OM protein.